Representasi Body Shaming Terhadap Perempuan Berkulit Gelap Dalam Iklan Wardah Di Youtube - Ema Nayla Zalianty; Cicilia Levina Putri Jelita; Khafka Adnin Nafiza Azzahra; Saphira Christi Adipati Ginting (CV. ITTC INDONESIA, 2025)
This research aims to critically analyze the representation of body shaming towards dark-skinned women in Wardah's cosmetics advertisement that aired on the YouTube platform, using the Norman Fairclough model Critical Discourse Analysis (AWK) approach. This approach is used to explore the power relationship hidden behind text and visuals, as well as how discursive practices in advertising also reproduce certain social structures, especially in the context of women's beauty construction in Indonesia. Through observation of a number of Wardah advertisements, a representation pattern was found that consistently highlights bright skin color as an ideal symbol of beauty, purity, and social success. On the other hand, dark skin is not shown explicitly as something negative, but is implicitly associated with deficiencies that need to be fixed through the use of whitening or skin brightening products. An advertising narrative that implies that the transformation of the skin from dark to light is a process towards a better version of the self, indirectly strengthens the ideology of discriminatory skin color, or known as colorism. This bias is not only symbolically detrimental, but also constructs the public perception that the dominant standard of beauty can only be achieved by moving away from the dark skin identity. This kind of representation has an impact on the marginalization of dark-skinned women, who often do not get space in mainstream media or are only shown as figures who have undergone changes towards